2021
DOI: 10.1080/19490976.2021.1897216
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial communities from patients with anorexia nervosa do not influence body weight in recipient germ-free mice

Abstract: Anorexia nervosa (AN) is a psychiatric disorder that presents with profound weight dysregulation, metabolic disturbances, and an abnormal composition of gut microbial communities. As the intestinal microbiota can influence host metabolism, the impact of enteric microbial communities from patients with AN on host weight and adiposity was investigated. Germ-free (GF) mice were colonized with fecal microbiotas from either patients with AN (n = 4) prior to inpatient treatment (AN T1, n = 50 recipient mice), the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Although our study does not address causality, recent studies transplanting fecal samples from patients with AN and non-ED controls into GF mice have addressed this phenomenon with mixed results. 11 , 22 The data reported here complement these studies by identifying specific bacterial taxa that may have a causative influence on host adiposity. Specifically, Bifidobacterium adolescentis and Faecalibacterium prausnitzii , depleted in patients with AN, are potential candidates to be used in gnotobiotic studies (mono-/dual-association or a consortium of microbes) coupled with calorie restriction, refeeding, or precision nutrition experiments to examine the contribution of enteric microbes to intestinal dysfunction in the context of nutrient deprivation.…”
Section: Discussionsupporting
confidence: 63%
“…Although our study does not address causality, recent studies transplanting fecal samples from patients with AN and non-ED controls into GF mice have addressed this phenomenon with mixed results. 11 , 22 The data reported here complement these studies by identifying specific bacterial taxa that may have a causative influence on host adiposity. Specifically, Bifidobacterium adolescentis and Faecalibacterium prausnitzii , depleted in patients with AN, are potential candidates to be used in gnotobiotic studies (mono-/dual-association or a consortium of microbes) coupled with calorie restriction, refeeding, or precision nutrition experiments to examine the contribution of enteric microbes to intestinal dysfunction in the context of nutrient deprivation.…”
Section: Discussionsupporting
confidence: 63%
“…The GF mice colonized with an AN microbiota exhibited decreased weight gain compared with mice colonized with non-AN control microbiotas. By contrast, Glenny et al [36] reported no differences in weight gain, fat or lean mass, or food consumption between GF mice colonized by gut microbiotas from AN patients and unaffected controls. Although both studies used a gnotobiotic (Greek; 'gnotos' meaning known and 'bios' meaning life) approach to address the same question, multiple technical differences could explain the diverging results.…”
Section: Intestinal Microbiotamentioning
confidence: 91%
“…Therefore, whether the changes in the intestinal microbiota found in patients with AN influence specific clinical hallmarks of the illness (i.e., weight dysregulation) or are merely a consequence of a nutrient-deprived environment warrants careful exploration. To date, most studies investigating the role of the gut microbiota in AN have compared gut microbial communities between patients with AN and unaffected controls [29][30][31][32][33][34]; however, only two studies have attempted to determine the influence of gut microbiotas from patients with AN on the host, with contrasting results [35,36].…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…Bacteria, such as Bacteroides vulgatus, may play a protective role against the development of pathologies specific to patients with AN. Recently, Glenny et al [ 59 ] reported that fecal transplantation from patients with AN exerted no significant effects on body weight in GF mice. A precise reason for this discrepant result is unclear; however, this may be related to the methodology of fecal transplantation, which involved the use of frozen feces, as they suggested.…”
Section: Introductionmentioning
confidence: 99%